Spatial and temporal localization of immune transcripts defines hallmarks and diversity in the tuberculosis granuloma - Berit Carow (Nature Portfolio, 2019)
Granulomas are a hallmark and focus of infective and immunological processes during infection with Mycobacterium tuberculosis. Here, Carow and colleagues show distinct spatial and temporal arrangement of immunological transcripts in tuberculosis granulomas.